Current problems of knowledge economy formation in modern conditions - Kocherbayeva, A.A.; Abildina, M.K.; Syzdykova, D.I. (Вестник Карагандинского университета, 2016)
The article examines theoretical aspects of the knowledge economy study. Characterized are the basic eco- nomic trends related to the production and dissemination of knowledge. The features and the internal regu- larities of calculation of the index of knowledge economy and the index of knowledge are determined. The basic directions of development and forms of knowledge economy display based on a comparative analysis of the index of knowledge economy in different countries are observed. The article analyzes the current state of knowledge economy index in Kyrgyzstan and Kazakhstan, the ways of further development of the knowledge economy in these countries.
Keywords: knowledge economy; knowledge economy index; innovation; science; human capital